2000
DOI: 10.1085/jgp.115.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Calcium Mobilization by Inositol 1,4,5-Trisphosphate in a Living Cell

Abstract: Changes in cytosolic free calcium ([Ca2+]i) often take the form of a sustained response or repetitive oscillations. The frequency and amplitude of [Ca2+]i oscillations are essential for the selective stimulation of gene expression and for enzyme activation. However, the mechanism that determines whether [Ca2+]i oscillates at a particular frequency or becomes a sustained response is poorly understood. We find that [Ca2+]i oscillations in rat megakaryocytes, as in other cells, results from a Ca2+-dependent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Both the rate and magnitude of intracellular calcium spikes are involved in essential molecular processes such as gene expression [ 89 ] and enzyme activation [ 90 ]. While it has long been shown that a steady increase in the frequency of calcium oscillations may lead to a sustained rise in intracellular Ca 2+ [ 91 , 92 ], the exact mechanism underlying the augmented frequency of Ca 2+ transients is yet to be elucidated [ 93 ]. Furthermore, although calcium spikes have been described at length in electrically excitable cells such as muscle (smooth, skeletal, cardiac) or neuronal cells, the same cannot be said for epithelial cells.…”
Section: Intracellular Calcium Regulation In Ovarian Physiology Anmentioning
confidence: 99%
“…Both the rate and magnitude of intracellular calcium spikes are involved in essential molecular processes such as gene expression [ 89 ] and enzyme activation [ 90 ]. While it has long been shown that a steady increase in the frequency of calcium oscillations may lead to a sustained rise in intracellular Ca 2+ [ 91 , 92 ], the exact mechanism underlying the augmented frequency of Ca 2+ transients is yet to be elucidated [ 93 ]. Furthermore, although calcium spikes have been described at length in electrically excitable cells such as muscle (smooth, skeletal, cardiac) or neuronal cells, the same cannot be said for epithelial cells.…”
Section: Intracellular Calcium Regulation In Ovarian Physiology Anmentioning
confidence: 99%